A new tumor suppressor role for the Notch pathway in bladder cancer - Rampias, T.; Vgenopoulou, P.; Avgeris, M.; Polyzos, A.; Stravodimos, K.; Valavanis, C.; Scorilas, A.; Klinakis, A (Nature Medicine, 2014)
The Notch signaling pathway controls cell fates through interactions between neighboring cells by positively or negatively affecting the processes of proliferation, differentiation and apoptosis in a context-dependent manner. This pathway has been implicated in human cancer as both an oncogene and a tumor suppressor. Here we report new inactivating mutations in Notch pathway components in over 40% of human bladder cancers examined. Bladder cancer is the fourth most commonly diagnosed malignancy in the male population of the United States. Thus far, driver mutations in fibroblast growth factor receptor 3 (FGFR3) and, less commonly, in RAS proteins have been identified. We show that Notch activation in bladder cancer cells suppresses proliferation both in vitro and in vivo by directly upregulating dual-specificity phosphatases (DUSPs), thus reducing the phosphorylation of ERK1 and ERK2 (ERK1/2). In mouse models, genetic inactivation of Notch signaling leads to Erk1/2 phosphorylation, resulting in tumorigenesis in the urinary tract. Collectively our findings show that loss of Notch activity is a driving event in urothelial cancer.
Keywords: Animals; Carcinoma, Transitional Cell/genetics/metabolism/pathology; Cell Line, Tumor; Cell Proliferation; Disease Models, Animal; Dual-Specificity Phosphatases/metabolism; Female; Gene Dosage; Genes, Tumor Suppressor; Humans; Male; MAP Kinase Signaling System; Mice; Mutation; Receptor, Notch1/deficiency/genetics/metabolism; Receptors, Notch/deficiency/genetics/*metabolism; signal transduction; Tumor Suppressor Proteins/deficiency/genetics/*metabolism; Urinary Bladder Neoplasms/genetics/*metabolism/pathology